Refocusing public health training on effective leadership and communication skills to increase efficacy - Phillips, Sharia; Hamilton, Jasmine; McCullough, Wayne; El Reda, Darline; Currier, Constance; Clements, John (Frontiers in Public Health, 2025)
Public health (PH) practitioners recognize the importance of cultivating future leaders, especially as the value of public health is increasingly scrutinized nationally. To address this scrutiny, the PH workforce must demonstrate through its leadership adept communication skills and informed conversations leading to decisions based on science. The Master of Public Health and other programs can play a crucial role in the development of these skills through training and experiential opportunities allowing students to practice and enhance their leadership and communication efficacy. This paper addresses how we start rethinking the way we train the next generation of PH professionals. It also focuses on leadership and effective communication and how we can upskill those currently in the profession to address communication challenges and therefore move the field forward.